Effects of a flavonoid-enriched orange peel extract against type 2 diabetes in the obese ZDF rat model - Alexander Gosslau; Emmanuel Zachariah; Shiming Li; Chi-Tang Ho (Food Science and Human Wellness)
Effects of an enriched orange peel extract (OPE) against type 2 diabetes (T2D) were analyzed in ZDF rats which were hyperglycemic, dyslipidemic and express pro-inflammatory markers. Glucose related parameters were lowered in the lean control and metformin group as compared to ZDF vehicle controls. OPE was well tolerated and induced a decline in fasted blood glucose and increase levels of fed glucose although to a lesser degree as compared to metformin. However, OPE did not improve glucose tolerance but showed significantly elevated glucose levels. Furthermore, OPE treatment caused an increase of free fatty acids in a dose-responsive manner as well as elevated levels of cholesterol and LDL. The analysis of inflammatory mediators revealed a significant down-regulation of COX-2, ICAM-1, and TNF-α in epididymal adipose tissue in response to OPE to a higher degree as compared to ibuprofen. In whole blood, IL-4 was upregulated in a dose-responsive manner as measured by ELISA. In summary, lipophilic OPE showed strong anti-inflammatory effects in adipose tissue, ambivalent effects against hyperglycemia, whereas hyperlipidemia was increased. Our study emphasize the complexity of anti-diabetic regimen suggesting a treatment with OPE to reduce inflammation in adipose tissue in combination with antidiabetic therapeutics as promising strategy against T2D. Keywords: Type 2 diabetes, Orange peel, Zucker diabetic fatty rats, Chronic inflammation, Obesity